AAHPERD - American Alliance for Health, Physical Education, Recreation and Dance (2006)
The American Alliance for Health, Physical Education, Recreation and Dance (AAHPERD) is the largest organization of professionals supporting and assisting those involved in physical education, leisure, fitness, dance, health promotion, and education and all specialties related to achieving a healthy lifestyle.